Determinants of willingness and actual participation in cocoa certification programs in Sierra Leone: Farmers and officers’ perspectives - Oladele, Oladimeji I.; Ngegba, Mohamed P.; Amara, Augustine; Sannoh, Bockarie I. (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2026)
This study addresses an important yet underexplored issue in agricultural development—distinguishing between willingness and actual participation in certification programs. This makes the research highly relevant for both policy and practice. The aim of the study is to investigate the factors influencing both farmers' and certification officers' willingness and actual involvement in cocoa certification initiatives in Sierra Leone. A multistage sampling technique was used to select the Kailahun District and the Kissi Tongi Chiefdom. Twenty cocoa farmers were randomly selected from each of the ten cocoa-producing communities in the chiefdom, resulting in a total sample size of 200 farmers. Thirty certification officers were also randomly chosen from the study area. Data were collected using a structured questionnaire, validated by experts, and analyzed using the Statistical Package for Social Sciences (SPSS) Version 29. Multiple linear regression, frequency counts, percentages, and Probit analysis were employed. The study’s results show that ethnicity (t = -3.01, p < 0.003), marital status (t = 1.81, p < 0.07), religion (t = 3.13, p < 0.002), and income (t = -6.26, p < 0.00) are factors that influence willingness to participate, while limitations on extension services (t = 1.86, p < 0.06), educational attainment (t = 3.69, p < 0.00), and extension service participation (t = 1.96, p < 0.05) are factors affecting actual participation. Based on these findings, it can be concluded that while technological factors determine actual involvement, significant sociocultural factors influence willingness to participate.